Leadership in Action: 360-Degree Feedback: The Leadership Challenges - Tornow, Walter; London, Manuel (Center for Creative Leadership, 1998)
At present it would be hard to find a Fortune 1000 company in the United States that hasn't tried 360-degree feedback somewhere in the organization at least once, and many are using it regularly.